The Effects of Personalized Nutrition Intervention In Breast Cancer Patients: A Systematic Review - Puspa Anindita Sidharta, Naomi (Jurnal Multidisiplin Indonesia, 2023)
Breast cancer is a common cancer in women worldwide. Personalized nutrition interventions have gained attention as a promising approach in the treatment of breast cancer. This systematic review aimed to evaluate their effectiveness. A comprehensive search of ScienceDirect and PubMed databases was conducted from 2018 to 2023 using the keyword "Personalized nutrition interventions for breast cancer." Six studies met the inclusion criteria. Results showed that dietary interventions led to improvements in body weight, metabolic parameters, and quality of life in breast cancer patients. The Mediterranean diet was associated with significant improvements in body weight, BMI, waist circumference, glycemia, and triglyceride levels, as well as a greater reduction in metabolic syndrome markers. The ketogenic diet resulted in significant weight loss due to fat mass reduction, while personalized and balanced diet interventions reduced the frequency of leukopenia and abdominal pain. A triple intervention program involving nutrition, exercise, and mindfulness positively impacted the quality of life in breast cancer survivors. Individualized diet therapy based on nutritional needs also significantly reduced barriers and improved nutritional status and quality of life in breast cancer patients undergoing chemotherapy. This review employed a systematic approach, including a comprehensive literature search, clear inclusion criteria, and thorough study quality assessment. In conclusion, personalized nutrition interventions can be effective for improving outcomes in breast cancer patients.